Determinants of Dropout Risk in Primary Education of Nepal: The Case of the Kathmandu Valley - Bajracharya, Dinu (Journal of Education and Research, 2019)
Even though the enrollment rate has been elevating in the primary education of Nepal, there are still numerous children who dropout from the school because of multifarious reasons that leads weighty impact for an individual and also to the society. Existing literature had already investigated key factors of dropout issues and educational intervention program after dropout in Nepal.